Intro stats - De Veaux, Richard D.; Velleman, Paul F., 1949-; Bock, David E. (Boston ; London : Pearson/Addison-Wesley, 2009)
Intro Stats, Third Edition, continues and extends the successful innovations pioneered in the DeVeaux/Velleman/Bock books, teaching statistics and statistical thinking for today's readers. This book uses a fun, conversational writing style, real data, and short, accessible chapters. The consistent Think/Show/Tell model for worked examples reinforces thinking about how to approach a statistics problem, showing how to solve it, and reporting the conclusion in the context of the problem.
I. Exploring and understanding data --- II. Exploring relationships between variables --- III. Gathering data --- IV. Randomness and probability --- V. From the data at hand to the world at large --- VI. Learning about the world --- VII. Inference when variables are related --- Appendices.
Previous ed.: Boston: Pearson/Addison Wesley, 2006.
Includes index.
Includes appendices.
Keywords: Statistics